DEMINERALIZATION OF CHITIN FROM VANNAME (Liptonaeus vannamei) SHRIMP SHELLWASTE USING CITRIC ACID AT DIFFERENT pH - Windi Ayu Maltadevi; Rahman Karnila; Edison Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACT Vanname shrimp (Liptonaeus vannamei) is widely consumed by the community, on the other hand, the skin waste is underutilized. Shrimp shell has a potential use as a chitin product. Chitin can be isolated from shrimp shell by demineralization and then deproteination their shells. The demineralization process was carried out using citric acid. This study aimed to determine the effect of different pH on the use of citric acid in the manufacture of chitin. The research method used was experimental composed as a non-factorial completely randomized design (CRD) with 3 treatment levels, namely K1(pH 4), K2(pH 5) and K3 (pH 6). The best characteristics of vannamei shrimp waste chitin with citric acid at pH 4 indicated by the highest yield of 48.82%, water content 2.18%, ash content 3.30%, and the degree of deacetylation of 40.3%. Keywords:Chitin, Citric acid, pH, Vanname shrimp